2017
DOI: 10.1111/tbed.12691
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of outbreaks of fowl adenovirus infections in commercial chickens in China

Abstract: SummaryOne hundred and five fowl adenovirus (FAdV) strains were isolated in China from 2015 to 2016 from poultry with inclusion body hepatitis (IBH) and hydropericardium syndrome (HPS). Polymerase chain reactions determined that 68 were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 23 publications
6
48
3
Order By: Relevance
“…This results in poor feed absorption with the consequent general symptoms [ 5 ]. FAdV-I was detected in young and old birds ( Table 4 and Table 5 ), corroborating results obtained previously [ 29 ], where the virus was found in several samples from broilers, layers, and domestic chickens of all ages, even though the clinical signs were more severe in younger birds [ 30 ]. ChPV infections affect young birds in their first four weeks [ 23 , 27 ], which is supported by our findings since the virus was detected in 20 infected samples from broilers between 1 and 28 days old ( Table 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…This results in poor feed absorption with the consequent general symptoms [ 5 ]. FAdV-I was detected in young and old birds ( Table 4 and Table 5 ), corroborating results obtained previously [ 29 ], where the virus was found in several samples from broilers, layers, and domestic chickens of all ages, even though the clinical signs were more severe in younger birds [ 30 ]. ChPV infections affect young birds in their first four weeks [ 23 , 27 ], which is supported by our findings since the virus was detected in 20 infected samples from broilers between 1 and 28 days old ( Table 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the positive rate of FAdV in 24 farms was still 75%, and the major genotype was FAdV-C4, indicating that silent infection may exist on these farms. What's more, consistent with previous studies (Niu et al, 2017), the FAdV-E7 was also popular in the farms with HRHS, but the pathogenicity about this stain was rare, and the effects of this virus on chickens need further analysis.…”
Section: Discussionsupporting
confidence: 85%
“…This results in poor feed absorption with the consequent general symptoms (JINDAL et al, 2009). FAdV-I was detected in young and old birds (Tables 10 and 11), corroborating results obtained previously (NIU et al, 2018), where the virus was found in several samples from broilers, layers, and domestic chickens of all ages, even though the clinical signs were more severe in younger birds (TORO et al, 2000). ChPV infections affect young birds in their first four weeks , which is supported by our findings since the virus was detected in 20 infected samples from broilers between 1 and 28 days old (Table 14).…”
Section: Phylogenetic Analysissupporting
confidence: 90%
“…IBV can be detected in the intestinal content, trachea, lung, liver, bursa of Fabricius, pancreas, thymus, kidney, proventriculus, and spleen of affected birds FAN et al, 2012), according to the dynamic distribution of the virus, resulting in a wide range of useful organs for molecular detection of this virus, which in our case helped to determine the presence of the pathogen in liver, intestine, pancreas, cloacal swabs, and caecal tonsils (Table 13). In our study, we found three different serotypes of FAdV-I, without ruling out the possibility of multiple FAdV infections in the same sample because multiple strains of different serotypes can affect to the same animal (NIU et al, 2018).…”
Section: Phylogenetic Analysiscontrasting
confidence: 51%